Investment-goods market power and capital accumulation - Fabio Bertolotti; Andrea Lanteri; Alessandro T. Villa (Federal Reserve Bank of Chicago, 2024)
We develop a model of capital accumulation in an open economy that imports investment goods from large foreign firms with market power. We model investmentgoods producers as a dynamic oligopoly and characterize a Markov Perfect Equilibrium with a Generalized Euler Equation. We use this optimality condition to analyze the joint evolution of investment, prices, and markups. The markup on investment goods decreases as the economy accumulates capital toward its steady state, generating a state-dependent capital adjustment cost. We analyze the role of commitment to future production of investment goods for the dynamics of markups and investment. We use a calibrated version of the model to simulate the effects of shocks to the demand for durable goods and semiconductors during the post-2020 world recovery. Finally, we perform counterfactual analyses on the effects of expanding the production capacity. The model highlights the separate roles of increasing marginal costs-akin to capacity constraints-and market power.
Keywords: 330